Long‐Term Interactions Between Intermediate Depth and Shallow Seismicity in North Chile Subduction Zone. Issue 18 (22nd September 2017) - Jara, Jorge; Socquet, Anne; Marsan, David; Bouchon, Michel
Abstract: We document interactions between intermediate depth and interplate seismicity in the North Chile subduction zone, over a 25 year period (1990–2015). We show that the 2005 M w 7.8 Tarapaca slab‐pull earthquake was followed by 9 years of enhanced deep and shallow seismicity, together with the decrease of eastward average GPS velocities and associated interplate coupling, eventually leading to the 2014 M w 8.1 Iquique megathrust earthquake. In contrast, megathrust ruptures (e.g., M w 8.0 Antofagasta in 1995, or M w 8.1 Iquique in 2014) initiate several years of silent background seismicity in the studied area, both at shallow and intermediate depths. The plunge of a rigid slab into a viscous asthenospheric mantle could explain the observed synchronization between deep and shallow seismicity and their long‐term interactions. Key Points: The 2005 slab‐pull earthquake triggered 9 years of deep‐shallow seismicity interactions, while megathrust ruptures initiate a seismic quiescence Post slab‐pull increased background seismicity is associated with a decrease in GPS eastward velocity, interpreted as interplate decoupling Bursts of deep and shallow seismicity are correlated in time, suggesting a lasting physical link between intraslab and interplate ruptures